The experimental contribution to the study of the portal circulation by means of dynamic hepatobiliary scintigraphy - Králík, J; Myslivećek, M; Neoral, C; Dusek, J; Grosmanová, T; Sprucek, F (Acta Universitatis Palackianae Olomucensis Facultatis Medicae, 1990)
Report is given on a group of dogs the portal vein of which was narrowed to 1/5 by putting on a metal spiral. A disorder of the circulation of the portal blood induced in this way was followed by opening of the effective hepatofugal collaterals and forming of slight portal hypertension without clinical manifestation. The changed portal circulation was studied by means of dynamic hepatobiliary scintigraphy within 12 months. It was found out that the curve of progression of the isotope through the liver had been changed in a way which corresponded to slowing of perfusion of the liver by the portal blood. It is analogous to observation of patients with PPH and its verification. The study is documented by morphological, X-ray and isotopic methods.
Keywords: regionální krevní průtok; Regional Blood Flow; portální systém; Hypertension, Portal; psi; Radionuclide Imaging; Animals; Liver; Biliary Tract; játra; Portal System; radioisotopová scintigrafie; portální hypertenze; zvířata; Dogs; žlučové ústrojí